Polyimide varnish with excellent voltage endurance property, and polyimide coating prepared therefrom

The polyimide varnish with nanosilica of controlled zeta potential addresses voltage durability issues, enhancing insulation properties and lifespan by improving dispersibility and preventing agglomeration.

JP2025010056AActive Publication Date: 2025-01-20PI ADVANCED MATERIALS CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2024105695
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-06-30
Filing Date
2024-06-28
Publication Date
2025-01-20
Estimated Expiration
2044-06-28

AI Technical Summary

Technical Problem

Existing polyimide coatings face challenges in withstanding high voltages, leading to issues such as corona discharge and premature insulation breakdown, which affects the durability and lifespan of electrical equipment.

Method used

A polyimide varnish is developed containing nanosilica with controlled zeta potential, which improves dispersibility and prevents agglomeration, enhancing voltage durability characteristics.

Benefits of technology

The polyimide varnish and its cured product exhibit significantly improved voltage durability, with increased breakdown voltage and extended insulation life, while maintaining low haze and mechanical strength.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025010056000001_ABST
    Figure 2025010056000001_ABST
Patent Text Reader

Abstract

To provide polyimide varnish with an excellent voltage endurance property.SOLUTION: Provided is polyimide varnish comprising: polyamic acid comprising a dianhydride monomer and a diamine monomer as polymerized units; and nanosilica; where the nanosilica has an absolute value of zeta potential of 10.0 mV to 40.0 mV.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a polyimide varnish and a polyimide coating produced therewith, and more particularly to a polyimide varnish having excellent voltage endurance characteristics and a polyimide coating produced therewith. [Background technology]

[0002] Generally, polyimide (PI) resin is a highly heat-resistant resin produced by solution polymerization of aromatic dianhydride and aromatic diamine or aromatic diisocyanate to produce polyamic acid derivatives, followed by ring-closing dehydration at high temperatures and imidization. Polyimide resin is an insoluble and infusible ultra-high heat-resistant resin with excellent properties such as thermal oxidation resistance, heat resistance, radiation resistance, low temperature properties, and chemical resistance. It is used in a wide range of fields, including heat-resistant advanced materials such as automotive materials, aviation materials, and spacecraft materials, as well as electronic materials such as insulating coating agents, insulating films, semiconductors, and electrode protection films for TFT-LCDs. Recently, it has also been used in display materials such as optical fibers and liquid crystal alignment films, and transparent electrode films, either by containing conductive fillers in the film or coating the surface.

[0003] In particular, insulated wires used as coil windings for motors and other devices, the insulating layer (insulating coating) that covers the conductor is required to have excellent insulation properties, adhesion to the conductor, heat resistance, mechanical strength, etc., and polyimide is used as the resin that forms the insulating layer.

[0004] However, in electrical equipment requiring high voltages, such as high-voltage motors, a high voltage is applied to the insulated wires that constitute the electrical equipment, and there is still a need to develop polyimides with excellent voltage durability that can withstand such high voltages.

[0005] Specifically, partial discharge (corona discharge) is likely to occur on the surface of the coating to which high voltage is applied, and if the occurrence of corona discharge causes a local temperature rise or the generation of ozone or ions, the coating of the insulated electric wire deteriorates, causing early dielectric breakdown and shortening the life of the electrical equipment. Therefore, in order to use polyimide as a coating material for conductors, particularly as a coating to which high voltage is applied, it is necessary to improve voltage endurance properties such as dielectric breakdown voltage performance and corona discharge inception voltage. Summary of the Invention [Problem to be solved by the invention]

[0006] The present invention provides a polyimide varnish having excellent voltage endurance characteristics.

[0007] The present invention also provides a polyimide produced by imidizing the polyimide varnish.

[0008] The present invention also provides a polyimide coating comprising a cured product of the polyimide varnish. [Means for solving the problem]

[0009] Since the present invention can be modified in various ways and can have various embodiments, a specific embodiment will be illustrated and described in detail. However, it should be understood that the present invention is not limited to the specific embodiment, and includes all modifications, equivalents, or alternatives included in the spirit and technical scope of the present invention.

[0010] The terms used in this application are merely used to describe certain embodiments and are not intended to limit the present invention. A singular expression includes a plural expression unless the context clearly indicates otherwise. In this application, the terms "include" or "have" are used to specify the presence of a feature, number, step, operation, component, part, or combination thereof described in the specification, and should be understood not to preclude the presence or additional possibility of one or more other features, numbers, steps, operations, components, parts, or combinations thereof.

[0011] When an amount, concentration, or other value or parameter is given herein as a range, a preferred range or a list of upper preferred values ​​and lower preferred values, that should be understood to specifically disclose all ranges formed by any pair of any upper range limit or preferred value and any lower range limit or preferred value, regardless of whether a range is otherwise disclosed.

[0012] When a range of numerical values ​​is recited herein, unless otherwise stated, the range includes its endpoints and limits within the range, and the scope of the invention is not intended to be limited to the specific values ​​recited when defining the range.

[0013] As used herein, "dianhydrides" is intended to include precursors or derivatives thereof, but may also be referred to as "dianhydride acids," "dianhydrides," or "acid dianhydrides." These may not technically be dianhydrides, but may nevertheless react with diamines to form polyamic acids, which may also be converted to polyimides.

[0014] As used herein, "diamine" is intended to include precursors or derivatives thereof which may not technically be diamines, but which nevertheless react with dianhydride acids to form polyamic acids, which can also be converted to polyimides.

[0015] Unless otherwise defined, all terms used herein, including technical or scientific terms, have the same meaning as commonly understood by a person of ordinary skill in the art to which the present invention belongs. Terms such as those defined in commonly used dictionaries should be interpreted as having a meaning consistent with the meaning they have in the context of the relevant art, and should not be interpreted in an ideal or overly formal sense unless expressly defined in this application. Specific contents for implementing the above invention are described as follows.

[0016] Polyimide Varnish The present invention relates to a polyimide varnish which has improved voltage endurance characteristics and can be used for conductor coating applications.

[0017] In one aspect of the present invention, there is provided a polyimide varnish comprising: a polyamic acid including polymerization units of a dianhydride monomer and a diamine monomer; and nanosilica, wherein the nanosilica has an absolute value of a zeta potential of 10.0 mV to 40.0 mV.

[0018] Nano Silica The polyimide varnish of the present invention may contain inorganic particles in order to improve physical properties such as voltage endurance characteristics. The inorganic particles are nanosilica, which are nano-sized silicon dioxide (SiO2) fine particles having an average particle diameter of 1000 nm or less, and the form and shape of the inorganic particles are not particularly limited.

[0019] The lower limit of the absolute value of the zeta potential may be 10.5 mV or more, 11.0 mV or more, 11.5 mV or more, 12.0 mV or more, 12.5 mV or more, 13.0 mV or more, 13.5 mV or more, 14.0 mV or more, 14.5 mV or more, or 15.0 mV or more, and the upper limit may be 38.0 mV or less, 35.0 mV or less, 32.0 mV or less, 30.0 mV or less, 28.0 mV or less, 27.0 mV or less, 26.0 mV or less, 25.0 mV or less, 24.0 mV or less, 23.5 mV or less, 23.0 mV or less, 22.5 mV or less, 22.0 mV or less, 21.0 mV or less, 20.5 mV or less, or 20.0 mV or less. By controlling the range of the absolute value of the zeta potential, it is possible to maintain high dispersibility without causing entanglement between nanosilica particles in the polyimide varnish, and thus to improve voltage durability characteristics (corona resistance). Here, the zeta potential is the zeta potential of nanosilica (silica sol) dispersed in an organic solvent, and the pH of the silica sol can be 2 to 12.

[0020] In one embodiment, the zeta potential of nanosilica dispersed in an organic solvent was measured using a Benano 180 zeta pro device manufactured by Bettersize, with the refractive index, viscosity, and dielectric constant of the organic solvent (dispersion medium) input into the device. The organic solvent may be any one selected from the group consisting of N-methylpyrrolidone (NMP), N-ethylpyrrolidone (NEP), dimethylacetamide (DMAc), dimethylformamide (DMF), and diethylformamide (DEF).

[0021] The organic solvent may have, for example, a refractive index of 1.2 to 1.6, a viscosity of 0.5 cP to 2.0 cP, and a dielectric constant of 30 to 40 at 25° C. Preferably, the refractive index of the organic solvent may be 1.3 to 1.5, a viscosity of 0.7 cP to 1.7 cP, and a dielectric constant of 32 to 39 at 25° C., more preferably, the refractive index of the organic solvent may be 1.35 to 1.47, a viscosity of 0.8 cP to 1.0 cP, and a dielectric constant of 35 to 38.5 at 25° C., and even more preferably, the refractive index of the organic solvent may be 1.4 to 1.45, a viscosity of 0.85 cP to 0.95 cP, and a dielectric constant of 37 to 38 at 25° C.

[0022] In one embodiment, nanosilica dispersed in dimethylacetamide (wherein the silica solids concentration is 30 wt %) can be used.

[0023] The zeta potential is the potential difference of colloidal particles suspended in a liquid. Particles dispersed in a solution are electrically charged with negative (-) or positive (+) charges on the surface, but the concentration of (+) ions increases around the (-) charged colloidal particles to form a fixed layer. Outside the fixed layer, there is a diffuse layer, where the concentration of (+) ions decreases and the (-) and (+) ions balance each other. The potential difference between the start point of the diffuse layer and the point where the (-) and (+) ions balance is the zeta potential. This zeta potential indicates the strength of the repulsive force between charged particles in the dispersion liquid, and is therefore used as a measure to evaluate the stability of the dispersed sol. The higher the (-) or (+) zeta potential value, the greater the electrical repulsive force between the particles, so the greater the distance between the particles, resulting in a stable state without aggregation. The zeta potential value can be used to confirm the measure of dispersion stability. In other words, the greater the absolute value of the zeta potential, the better the dispersibility. In addition, the zeta potential values ​​may differ depending on the solvent, concentration, pH, functional group, and surface properties of the particles, and it is preferable to compare them as a measure of stability.

[0024] The nanosilica may have an average particle size of 1 to 200 nm, specifically, for example, 5 to 150 nm, 5 to 100 nm, 5 to 70 nm, 10 to 50 nm, or 10 to 30 nm. The average particle size may be measured by equipment such as BET, SEM, or zeta potential.

[0025] The nanosilica may also be nanosilica surface-modified with an organosilane.

[0026] In addition, the organic silane of the nanosilica surface-modified with an organic silane is methyltrimethoxysilane, hexamethyldisiloxane, n-octyltrimethoxysilane, n-octyltriethoxysilane, isooctyltrimethoxysilane, dodecyltrimethoxysilane, octadecyltrimethoxysilane, propyltrimethoxysilane, hexyltrimethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-acryloxypropyltrimethoxysilane, 3-(methacryloxy)propyltriethoxysilane, 3-(methacryloxy)propylmethyldimethoxysilane, 3-(acryloxypropyl)methyldimethoxysilane, 3-(methacryloxy)propyl ... Propyldimethylethoxysilane, styrylethyltrimethoxysilane, phenyltriethoxysilane, p-tolyltriethoxysilane, vinylmethyldiacetoxysilane, vinyldimethylethoxysilane, vinylmethyldiethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, vinyltriacetoxysilane, vinyltriisopropoxysilane, vinyltriphenoxysilane, vinyltri-t-butoxysilane, vinyltris(isobutoxy)silane, vinyltriisoprophenoxysilane, vinyltris(2-methoxyethoxy)silane, diisopropylethylamine phenyltrimethoxysilane (N,N-Diisopropylethylamine The silane may include one or more selected from the group consisting of N-phenyl-3-aminopropyltrimethoxysilane (PAPTES), N-phenyl-3-aminopropyltrimethoxysilane (PPTMS ...

[0027] In addition, the nanosilica surface-modified with the organic silane may be a compound having at least one phenyl group at the end of the surface of the nanosilica and a compound having at least one amine group, hydroxyl group, thiol group, or epoxide group at the end. Specifically, the compound having at least one phenyl group at the end may be phenyltrimethoxysilane (PTMS) or phenylaminopropyltrimethoxysilane (PAPTES). In addition, the compound having at least one amine group, hydroxyl group, thiol group, or epoxide group at the end may be glycidoxypropyltrimethoxysilane (GPTMS) or aminopropyltrimethoxysilane (APTMS).

[0028] The nanosilica surface-modified with the organic silane can be produced by surface-treating the nanosilica with the organic silane. For example, the organic silane is heated under acidic or basic conditions and surface-treated for about 1 to 24 hours to obtain nanosilica. The surface modification may also be achieved by other known methods, for example, by mixing the organic silane with a solvent and reacting at a temperature of 10 to 100°C or 20 to 60°C for 1 to 10 hours or 1 to 5 hours to obtain surface-modified nanosilica. To bond two or more compounds to the surface of the nanosilica, each of the above methods can be performed.

[0029] The nanosilica surface-modified with the organic silane of the present invention prevents the aggregation of inorganic particles in the polyimide varnish, and the functional groups of the compound enhance the interaction with the solid content (polyamic acid), thereby improving dispersibility and miscibility.

[0030] The nanosilica may be contained in an amount of 4 to 30 parts by weight based on 100 parts by weight of the polyimide solid content contained in the entire polyimide varnish. For example, the lower limit of the nanosilica content may be 4.3 parts by weight or more, 4.5 parts by weight or more, 4.8 parts by weight or more, 5.0 parts by weight or more, 5.3 parts by weight or more, 5.5 parts by weight or more, 5.7 parts by weight or more, 5.8 parts by weight or more, or 5.9 parts by weight or more. The upper limit of the nanosilica content may be 25 parts by weight or less, 20 parts by weight or less, 19 parts by weight or less, 18 parts by weight or less, 17 parts by weight or less, 16 parts by weight or less, 15 parts by weight or less, 14.5 parts by weight or less, 14 parts by weight or less, 13.5 parts by weight or less, 13.3 parts by weight or less, or 13 parts by weight or less. If the content of the nanosilica is less than 4 parts by weight, it is not effective in improving the voltage endurance characteristics, and if it exceeds 30 parts by weight, it is not preferable because the physical properties may be deteriorated.

[0031] Polyamic Acid In the present invention, the dianhydride monomer is pyromellitic dianhydride (PMDA), biphenyl tetracarboxylic dianhydride (BPDA), benzophenone tetracarboxylic dianhydride (BTDA), oxydiphthalic dianhydride (ODPA), diphenylsulfone-3,4,3',4'-tetracarboxylic dianhydride (DSDA), bis(3,4-dicarboxyphenyl)sulfide dianhydride, 2,2-bis(3,4-dicarboxyphenyl)-1,1,1,3,3,3-hexafluoropropane dianhydride, 2,3,3',4'-benzophenone tetracarboxylic dianhydride, bis(3,4-dicarboxyphenyl)methane dianhydride, 2,2-bis(3,4-dicarboxyphenyl)propane dianhydride, p-phenylene bis(trimeristic monoester acid anhydride), The compound may include one or more selected from the group consisting of p-biphenylene bis(trimeristic monoester acid anhydride), m-terphenyl-3,4,3',4'-tetracarboxylic dianhydride, p-terphenyl-3,4,3',4'-tetracarboxylic dianhydride, 1,3-bis(3,4-dicarboxyphenoxy)benzene dianhydride, 1,4-bis(3,4-dicarboxyphenoxy)benzene dianhydride, 1,4-bis(3,4-dicarboxyphenoxy)biphenyl dianhydride, 2,2-bis[(3,4-dicarboxyphenoxy)phenyl]propane dianhydride (BPADA), 2,3,6,7-naphthalene tetracarboxylic dianhydride, 1,4,5,8-naphthalene tetracarboxylic dianhydride, and 4,4'-(2,2-hexafluoroisopropylidene)diphthalic dianhydride.

[0032] Specifically, the dianhydride monomer may include one or more selected from the group consisting of pyromellitic dianhydride (PMDA), biphenyltetracarboxylic dianhydride (BPDA) and benzophenonetetracarboxylic dianhydride (BTDA), and may preferably include pyromellitic dianhydride (PMDA).

[0033] The diamine monomer may be 1,4-diaminobenzene (PPD), 4,4'-diaminodiphenyl ether (ODA), 2,2-bisaminophenoxyphenylpropane (BAPP), metaphenylenediamine, 3,3'-dimethylbenzidine, 2,2'-dimethylbenzidine, 2,4-diaminotoluene, 2,6-diaminotoluene, 3,5-diaminobenzoic acid (DABA), 3,4'-diaminodiphenyl ether, 4,4'-diaminodiphenylmethane (MDA), 3,3'-dimethyl-4,4'-diaminobiphenyl, 2,2'-dimethyl m-tolidine, 2,2'-bis(trifluoromethyl)-4,4'-diaminobiphenyl, 3,3'-dimethyl-4,4'-diaminodiphenylmethane, 3,3'-dicarboxy-4,4'-diaminodiphenylmethane, 3,3',5,5'-tetramethyl-4,4'-diaminodiphenylmethane, bis(4-aminophenyl)sulfide, 4,4'-diaminobenzanilide, 3,3'-dimethoxybenzidine, 2,2'-dimethoxybenzidine, 3,3'-diaminodiphenyl ether, 3,3'- Diaminodiphenyl sulfide, 3,4'-diaminodiphenyl sulfide, 4,4'-diaminodiphenyl sulfide, 3,3'-diaminodiphenyl sulfone, 3,4'-diaminodiphenyl sulfone, 4,4'-diaminodiphenyl sulfone, 3,3'-diaminobenzophenone, 4,4'-diaminobenzophenone, 3,3'-diamino-4,4'-dichlorobenzophenone, 3,3'-diamino-4,4'-dimethoxybenzophenone, 3,3'-diaminodiphenylmethane, 3,4'-diaminodiphenylmethane, 2,2-bis(3-aminodiphenyl) 2,2-bis(4-aminophenyl)propane, 2,2-bis(3-aminophenyl)-1,1,1,3,3,3-hexafluoropropane, 2,2-bis(4-aminophenyl)-1,1,1,3,3,3-hexafluoropropane, 3,3'-diaminodiphenyl sulfoxide, 3,4'-diaminodiphenyl sulfoxide, 4,4'-diaminodiphenyl sulfoxide, 1,3-bis(3-aminophenyl)benzene, 1,3-bis(4-aminophenyl)benzene, 1,4-bis(3-aminophenyl)benzene, 1,4-bis(4-aminophenyl)benzene, 1,3-bis(4-aminophenoxy)benzene (TPE-R), 1,4-bis(3-aminophenoxy)benzene (TPE-Q), 1,3-bis(3-aminophenoxy)-4-trifluoromethylbenzene, 3,3'-diamino-4-(4-phenylphenoxy)benzophenone, 3,3'-diamino-4,4'-di(4-phenylphenoxy)benzophenone, 1,3-bis(3-aminophenylsulfide)benzene, 1,3-bis(4-aminophenylsulfide)benzene, 1,4-bis(4-aminophenylsulfide) 1,3-bis(3-aminophenylsulfone)benzene, 1,3-bis(4-aminophenylsulfone)benzene, 1,4-bis(4-aminophenylsulfone)benzene, 1,3-bis[2-(4-aminophenyl)isopropyl]benzene, 1,4-bis[2-(3-aminophenyl)isopropyl]benzene, 1,4-bis[2-(4-aminophenyl)isopropyl]benzene, 3,3'-bis(3-aminophenoxy)biphenyl, 3,3'-bis(4-aminophenoxy)biphenyl, 4,4'-bis(3-aminophenoxy)biphenyl, 4,4'-bis(4-aminophenoxy)biphenyl, bis[3-(3-aminophenoxy)phenyl]ether, bis[3-(4-aminophenoxy)phenyl]ether, bis[4-(3-aminophenoxy)phenyl]ether, bis[4-(4-aminophenoxy)phenyl]ether, bis[3-(3-aminophenoxy)phenyl]ketone, bis[3-(4-aminophenoxy)phenyl]ketone, bis[4-(3-aminophenoxy)phenyl]ketone, bis[4-(4-amino phenoxy)phenyl]ketone, bis[3-(3-aminophenoxy)phenyl]sulfide, bis[3-(4-aminophenoxy)phenyl]sulfide, bis[4-(3-aminophenoxy)phenyl]sulfide, bis[4-(4-aminophenoxy)phenyl]sulfide, bis[3-(3-aminophenoxy)phenyl]sulfone, bis[3-(4-aminophenoxy)phenyl]sulfone, bis[4-(3-aminophenoxy)phenyl]sulfone, bis[4-(4-aminophen 2,2-bis[3-(3-aminophenoxy)phenyl]propane, 2,2-bis[3-(4-aminophenoxy)phenyl]propane, 2,2-bis[4-(3-aminophenoxy)phenyl]propane, 2,2-bis[3-( The fluorocarbon polymer may include one or more selected from the group consisting of 2,2-bis[3-(4-aminophenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane, 2,2-bis[4-(3-aminophenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane, and 2,2-bis[4-(4-aminophenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane.

[0034] Specifically, the diamine monomer may include one or more selected from the group consisting of 1,4-diaminobenzene (PPD), 4,4'-diaminodiphenyl ether (ODA), 2,2-bisaminophenoxyphenylpropane (BAPP) and 1,3-bis(4-aminophenoxy)benzene (TPE-R), and preferably includes 4,4'-diaminodiphenyl ether (ODA).

[0035] The polyamic acid can include polymerized units of pyromellitic dianhydride (PMDA) and 4,4'-diaminodiphenyl ether (ODA).

[0036] In the present invention, pyromellitic dianhydride (PMDA) may be contained in a ratio of 50 mol% or more of the total dianhydride monomers, specifically, 60 mol% or more, 70 mol% or more, 75 mol% or more, 80 mol% or more, 85 mol% or more, 90 mol% or more, 95 mol% or more, 99 mol% or more, or 100 mol% or more.

[0037] In addition, 4,4'-diaminodiphenyl ether (ODA) may be contained in a ratio of 50 mol% or more of the total diamine monomers, specifically, 60 mol% or more, 70 mol% or more, 75 mol% or more, 80 mol% or more, 85 mol% or more, 90 mol% or more, 95 mol% or more, 99 mol% or more, or 100 mol% or more.

[0038] In the polyamic acid of the present invention, the dianhydride monomer may be 95 to 105 mol % relative to 100 mol % of the diamine monomer. For example, the lower limit may be 96 mol % or more, 97 mol % or more, 98 mol % or more, 99 mol % or more, or 99.5 mol % or more, and the upper limit may be 104 mol % or less, 103 mol % or less, 102 mol % or less, 101 mol % or less, or 100.5 mol % or less.

[0039] The molar ratio of the dianhydride monomer to the diamine monomer may be 6:4 to 4:6, preferably 5.5:4.5 to 4.5:6.5, and more preferably 5:5.

[0040] The polyimide varnish may have a polyimide solid content of 10 to 50% by weight. The lower limit of the polyimide solid content may be, for example, 13% by weight or more, 15% by weight or more, 18% by weight or more, 20% by weight or more, or 25% by weight or more, and the upper limit may be, for example, 48% by weight or less, 45% by weight or less, 43% by weight or less, 40% by weight or less, 38% by weight or less, 35% by weight or less, 33% by weight or less, or 30% by weight or less. By adjusting the polyimide solid content of the polyimide varnish, it is possible to control the increase in viscosity and shorten the process time during the curing process.

[0041] Organic solvents In the present invention, the polyimide varnish further includes an organic solvent. The organic solvent is not particularly limited as long as it is an organic solvent in which polyamic acid can be dissolved, and as one example, the organic solvent may be an aprotic polar solvent.

[0042] Specifically, the organic solvent may include one or more selected from the group consisting of N-methyl-pyrrolidone (NMP), N,N'-dimethylformamide (DMF), N,N'-diethylformamide (DEF), N,N'-dimethylacetamide (DMAc), dimethylpropanamide (DMPA), N,N-diethylacetamide (DEAc), dimethylsulfoxide (DMSO), 3-methoxy-N,N-dimethylpropanamide (KJCMPA), p-chlorophenol, o-chlorophenol, γ-butyrolactone (GBL), diglyme, and naphthalene. Preferably, N-methyl-pyrrolidone (NMP), N,N'-dimethylformamide (DMF), N,N'-dimethylacetamide (DMAc), dimethylsulfoxide (DMSO), etc. may be used.

[0043] In addition, the organic solvent may further include a modifier containing a hydroxyl group (OH) or an amine group (NH), and examples of the modifier containing a hydroxyl group (OH) or an amine group (NH) include ethylamine, triethanolamine, dimethylamine, trimethylamine, diethylenetriamine, ethylenediamine, tributylamine, pyridine, pyrrolidine, methanol, ethanol, propanol, isopropanol, sec-butanol, tert-butanol, n-amyl alcohol, isoamyl alcohol, hexanol, octanol, capryl alcohol, nonyl alcohol, decyl alcohol, undecyl alcohol, lauryl alcohol, myristyl alcohol, cetyl alcohol, stearyl alcohol, allyl alcohol, crotyl alcohol, propargyl alcohol, ethylene glycol, propylene glycol, benzyl alcohol, and phenol. The modifier may react with the dianhydride monomer to control the reactivity.

[0044] Polyimide varnish and its cured product The polyimide varnish is heated at 30° C. for 1 s. -1 The viscosity measured under the condition of a shear rate of 1 / s may be in the range of 500 cP to 20,000 cP. For example, the upper limit may be 20,000 cP, 15,000 cP, or 10,000 cP or less. The lower limit is not particularly limited, but may be 1,000 cP, 1,200 cP, 1,500 cP, or 1,800 cP or more. In one embodiment, the viscosity may be measured using a Rheostress 600 manufactured by Haake Co., Ltd., and may be measured under the conditions of a shear rate of 1 / s, a temperature of 30° C., and a plate gap of 1 mm. The present invention can provide a polyimide varnish having excellent processability by adjusting the viscosity range.

[0045] The polyimide varnish may have a haze of 1.5% or less. For example, the upper limit of the haze may be 1.4% or less, 1.3% or less, 1.2% or less, 1.1% or less, 1% or less, 0.9% or less, or 0.8% or less, and the lower limit may be, but is not limited to, more than 0%, 0.05% or more, or 0.1% or more. In one embodiment, the haze is measured according to ASTM E308 using equipment manufactured by HunterLab.

[0046] Also, the polyimide obtained by curing the polyimide varnish may have a haze of 1.5% or less. For example, the upper limit of the haze may be 1.4% or less, 1.3% or less, 1.2% or less, 1.1% or less, 1% or less, 0.9% or less, 0.8% or less, 0.7% or less, 0.6% or less, or 0.5%, and the lower limit may be, but is not limited to, more than 0%, 0.05% or more, or 0.1% or more. In one embodiment, the haze is measured according to ASTM E308 using equipment manufactured by HunterLab, and the thickness of the polyimide is 20±1.0 μm.

[0047] Furthermore, the polyimide varnish and its cured product of the present invention use nanosilica having a predetermined absolute value range of zeta, which prevents aggregation of the nanosilica in the polyimide varnish and has excellent dispersibility, thereby achieving a low level of haze.

[0048] In addition, the polyimide obtained by curing the polyimide varnish may have an elongation of 25% or more, and the lower limit of the elongation may be, for example, 30%, 33%, 35%, 36%, 37%, 38%, or 39% or more. The upper limit is not particularly limited, but may be 80% or less. In one embodiment, the elongation may be measured according to ASTM D-882 method using an Instron 5564 UTM device manufactured by Instron Corporation after curing the polyimide varnish into a polyimide film and cutting it into a width of 10 mm and a length of 40 mm.

[0049] In addition, the polyimide obtained by curing the polyimide varnish may have a tensile strength of 100 MPa or more, and the lower limit of the tensile strength may be, for example, 105 MPa, 110 MPa, 115 MPa, 120 MPa, 124 MPa, or 128 MPa or more. The upper limit is not particularly limited, but may be 400 MPa or less. The tensile strength was measured using an Instron 5564 UTM device manufactured by INSTRON Corporation, with samples having a length of 500 mm and a width of 10 mm prepared, at a speed of 50 mm / min, and the average of 10 samples was calculated.

[0050] In another aspect of the present invention, there is provided a cured polyimide product obtained by curing the polyimide varnish, and the cured polyimide product may be a polyimide film.

[0051] The polyimide cured product may have a voltage endurance characteristic, which is the time that an insulating material can withstand a predetermined voltage according to IEC-60851-5, of 300 minutes or more, and the lower limit of the voltage endurance characteristic may be, for example, 330 minutes or more, 370 minutes or more, 400 minutes or more, 450 minutes or more, 500 minutes or more, 550 minutes or more, 600 minutes or more, 650 minutes or more, 700 minutes or more, 720 minutes or more, 750 minutes or more, 770 minutes or more, 800 minutes or more, 820 minutes or more, or 830 minutes or more. The upper limit is not particularly limited, but may be 3,000 minutes or less. The voltage endurance characteristic was measured by connecting the polyimide coating to a jig, applying a voltage of AC 1.5 kV (frequency 60 Hz), and measuring the time until a leak current of 5 mA or more was detected. Here, the thickness of the polyimide may be 26±1.0 μm.

[0052] Furthermore, the polyimide varnish of the present invention and its cured product were able to improve voltage endurance characteristics by using nanosilica having an absolute value range of a predetermined zeta range.

[0053] The polyimide cured product may have a dielectric breakdown voltage (BDV) of 200 kV / mm or more as measured according to the ASTM D149 standard, and the lower limit of the dielectric breakdown voltage may be, for example, 205 kV / mm or more, 210 kV / mm or more, 215 kV / mm or more, 220 kV / mm or more, 225 kV / mm or more, 230 kV / mm or more, 233 kV / mm or more, 235 kV / mm or more, 238 kV / mm or more, 240 kV / mm or more, 241 kV / mm or more, or 242 kV / mm or more. The upper limit is not particularly limited, but may be 500 kV / mm or less.

[0054] In another aspect of the present invention, there is provided a polyimide prepared by imidizing the polyimide varnish, and the polyimide may be in the form of a film.

[0055] In another aspect of the present invention, there is provided a polyimide coating comprising the above-mentioned cured polyimide.

[0056] In one embodiment, a method for producing the polyimide coating may include the steps of coating a surface of a conductor with a polyimide varnish and imidizing the polyimide varnish coated on the surface of the conductor.

[0057] The conductor may be a copper wire made of copper or a copper alloy, but may also be a conductor made of other metal materials such as a silver wire, or various metal-plated wires such as aluminum or tin-plated wire. The thickness of the conductor and the coating may conform to the KS C3107 standard. The diameter of the conductor may be within a range of 0.3 to 3.2 mm, and the standard coating thickness of the coating (average value of the maximum coating thickness and the minimum coating thickness) may be 21 to 194 μm for type 0, 14 to 169 μm for type 1, and 10 to 31 μm for type 2. The cross-sectional shape of the conductor may be, but is not limited to, a ring wire, a rectangular wire, a hexagonal wire, etc.

[0058] In another aspect of the present invention, there is provided an electric wire comprising the polyimide coating.

[0059] Specifically, the coated electric wire may include a polyimide coating produced by coating the surface of an electric wire with the polyimide varnish and imidizing the polyimide varnish. In one specific example, the coated electric wire may include an electric wire and a coating formed by coating the surface of the electric wire with the polyimide and imidizing the polyimide.

[0060] The present application can also provide an electronic device including the coated electric wire. The electronic device can be, for example, an electric motor.

[0061] In another aspect of the present invention, a part is provided that includes a molded body formed from a polyimide varnish.

[0062] Specifically, the parts can be electronic circuit board parts, semiconductor devices, lithium ion battery parts, solar cell parts, fuel cell parts, motor windings, engine peripheral parts, paints, optical parts, heat dissipation materials, electromagnetic wave shielding materials, surge parts, dental materials, slide coatings, and electrostatic chucks. Effect of the Invention

[0063] The polyimide varnish of the present invention has the effect of being excellent in voltage durability characteristics and also excellent in physical properties such as polyimide haze.

[0064] In addition, the present invention has an effect of being highly applicable to conductor coating for use in windings for electric vehicles (EVs). [Brief description of the drawings]

[0065] [Figure 1] 2 shows SEM images of polyimide cured films according to Example 2-1 and Comparative Example 2-1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0066] In order to facilitate understanding of the present invention, examples are presented. The following examples are provided to facilitate understanding of the present invention, and are not intended to limit the scope of the present invention. EXAMPLES

[0067] <Example> Production Example 1. Nanosilica surface-treated with organic silane 1 Nanosilica 1 (dimethylacetamide dispersed silica sol, silica solid concentration 30wt%, silica average particle size 10-30nm, average zeta potential (absolute value) 17.86mV) surface-treated with organic silane was prepared. Here, the zeta potential was measured twice using a Bettersize Benano180 zeta pro device by inputting the refractive index, viscosity, and dielectric constant of dimethylacetamide into the device, and the value was obtained by arithmetic averaging.

[0068] Comparative Production Example 1. Nanosilica Nanosilica (N-methylpyrrolidone dispersed silica sol, silica solid concentration 30wt%, silica average particle size 10-20nm, average zeta potential (absolute value) 8.42mV) was prepared. Here, the zeta potential was measured twice using a Bettersize Benano180 zeta pro device by inputting the refractive index, viscosity, and dielectric constant of N-methylpyrrolidone into the device, and the value was obtained by arithmetic averaging.

[0069] Comparative Example 2: Nanosilica 2 surface-treated with organic silane Nanosilica 2 (dimethylacetamide dispersed silica sol, silica solids concentration 30wt%, average silica particle size 10-20nm, average zeta potential (absolute value) 4.59mV) surface-treated with organic silane was prepared. Here, the zeta potential was measured twice using a Bettersize Benano180 zeta pro device by inputting the refractive index, viscosity, and dielectric constant of dimethylacetamide into the device, and the value was obtained by arithmetic averaging.

[0070] Comparative Example 3: Nanosilica 3 surface-treated with organic silane Nanosilica 3 (dimethylacetamide dispersed silica sol, silica solids concentration 30wt%, average silica particle size 10-20nm, average zeta potential (absolute value) 1.51mV) surface-treated with organic silane was prepared. Here, the zeta potential was measured twice using a Bettersize Benano180 zeta pro device by inputting the refractive index, viscosity, and dielectric constant of dimethylacetamide into the device, and the value was obtained by arithmetic averaging.

[0071] Example 1. Polyimide varnish Example 1-1 An organic solvent containing dimethylacetamide (DMAc) and a modifier (0-2 mol%) was added to a reaction vessel replaced with nitrogen gas, and nanosilica surface-treated with an organic silane according to Preparation Example 1 (6 wt% based on polyimide solids) and pyromellitic dianhydride (PMDA) (92 mol%) as a dianhydride monomer were mixed and stirred at 40°C for 30 minutes. Next, 4,4'-diaminodiphenyl ether (ODA) (100 mol%) and pyromellitic dianhydride (PMDA) (8 mol%) were added as diamine monomers, and the mixture was stirred and polymerized at 40°C for about 1 hour to produce a polyimide varnish (polyimide solids 25 wt%).

[0072] Example 1-2 A polyimide varnish was produced in the same manner as in Example 1, except that instead of using the nanosilica surface-treated with an organosilane (6% by weight based on the polyimide solid content) in Example 1, nanosilica surface-treated with an organosilane (12% by weight based on the polyimide solid content) was used.

[0073] Comparative Examples 1-1 to 1-3 A polyimide varnish was prepared in the same manner as in Example 1-1, except that the components and content ratios of the dianhydride monomer, the diamine monomer, and the nanosilica surface-treated with an organic silane were adjusted as shown in Table 1 below.

[0074] [Table 1]

[0075] Example 2. Polyimide cured product (polyimide film) Example 2-1 The polyimide varnish prepared in Example 1-1 was rotated at a high speed of 2,000 rpm to remove air bubbles, and then the degassed polyimide varnish was applied onto a glass substrate (230 mm×230 mm, thickness: 0.55 mm) using a spin coater.

[0076] The mixture was then cured under a nitrogen atmosphere at 110°C (20 min) → 150°C (20 min) → 200°C (20 min) → 300°C (20 min) to obtain a polyimide cured film (thickness 20±1.0 μm or 26±1.0 μm).

[0077] Example 2-2 A cured polyimide material was prepared in the same manner as in Example 2-1, except that the polyimide varnish of Example 1-2 was used instead of the polyimide varnish of Example 1-1 in Example 2-1.

[0078] Comparative Example 2-1 A cured polyimide material was prepared in the same manner as in Example 2-1, except that the polyimide varnish of Comparative Example 1-1 was used instead of the polyimide varnish of Example 1-1 in Example 2-1.

[0079] Comparative Example 2-2 A cured polyimide material was prepared in the same manner as in Example 2-1, except that the polyimide varnish of Comparative Example 1-2 was used instead of the polyimide varnish of Example 1-1 in Example 2-1.

[0080] Comparative Example 2-3 A cured polyimide material was prepared in the same manner as in Example 2-1, except that the polyimide varnish of Comparative Example 1-3 was used instead of the polyimide varnish of Example 1-1 in Example 2-1.

[0081] Example 3. Polyimide coating Example 3-1 The polyimide varnish according to Example 1-1 was applied to a rectangular copper wire 20 to 28 times in a coating and curing oven, followed by drying and curing, to produce an electric wire having a polyimide coating with a coating thickness of 110±10 μm.

[0082] Example 3-2 A polyimide coating was produced in the same manner as in Example 3-1, except that the polyimide varnish in Example 1-2 was used instead of the polyimide varnish in Example 1-1.

[0083] <Experimental Example> Experimental example 1. SEM analysis The polyimide film-type cured products of Example 2-1 and Comparative Example 2-1 were analyzed using a scanning electron microscope, VEGA3 manufactured by TESCAN, and the SEM images are shown in FIG.

[0084] According to FIG. 1, in the case of Comparative Example 2-1, 200 nm particles were confirmed, which are particles of nanosilica aggregates. On the other hand, in the case of Example 2-1, it was confirmed that the nanosilica was uniformly dispersed without aggregation. Therefore, it was found that there is a difference in the degree of dispersion and aggregation of nanosilica depending on the absolute value of the zeta potential.

[0085] Experimental example 2. Physical property evaluation The polyimide varnishes prepared in Examples 1-1, 1-2, and Comparative Examples 1-1 and 1-2 were cured to obtain the cured products of Examples 2-1, 2-2, and Comparative Examples 2-1 and 2-2, and the physical properties were examined by the following methods. The results are shown in Tables 2 and 3.

[0086] (1) Voltage endurance characteristics The polyimide films (thickness 26±1.0 μm) of Examples 2-1 and 2-2 and Comparative Example 2-1 were connected to a jig, and a voltage of AC 1.5 kV (frequency 60 Hz) was applied to measure the time until a leak current of 5 mA or more was detected, and the voltage endurance characteristics were measured in accordance with IEC-60851-5. The results are shown in Table 2 below.

[0087] (2) Haze The haze of the polyimide varnishes (Examples 1-1 and 1-2, and Comparative Examples 1-1 to 1-3) was measured in accordance with ASTM E308 using equipment manufactured by HunterLab, and the results are shown in Table 3 below.

[0088] [Table 2]

[0089] [Table 3]

[0090] As shown in Table 2, by using nanosilica having a zeta potential within a certain range, it was confirmed that the voltage durability characteristics of the polyimide varnish of the present invention and its cured film form are significantly improved by about 3 times or more compared to Comparative Example 2-1.

[0091] Also, according to Table 3, the polyimide varnish of the present invention and its film-shaped cured product were both able to achieve low levels of haze. Specifically, in the case of the varnish, Examples 1-1 and 1-2 had a haze of 0.6%, which is about 4 to 10 times lower than Comparative Examples 1-1 to 1-3, meaning that the nanosilica was not aggregated and was uniformly dispersed. In Comparative Examples 1-1 to 1-3, the haze increased due to aggregation of substances in the varnish, which may cause deterioration of mechanical properties and quality.

[0092] This specification omits detailed descriptions of contents that can be fully recognized and inferred by a person having ordinary skill in the technical field of the present invention, and various modifications are possible within the scope of the present invention, other than the specific examples described in this specification, without changing the technical idea or essential configuration of the present invention. Therefore, the present invention can be implemented in a manner different from that specifically described and exemplified in this specification, and this is something that can be understood by a person having ordinary skill in the technical field of the present invention.

Claims

1. a polyamic acid containing a dianhydride monomer and a diamine monomer as polymerization units; and nanosilica, The nanosilica has an absolute value of a zeta potential of 10.0 mV to 40.0 mV.

2. 2. The polyimide varnish according to claim 1, wherein the nanosilica has an average particle size of 1 to 200 nm.

3. 2. The polyimide varnish according to claim 1, wherein the nanosilica is an organosilane surface-modified nanosilica.

4. The organic silane of the nanosilica surface-modified with an organic silane is methyltrimethoxysilane, hexamethyldisiloxane, n-octyltrimethoxysilane, n-octyltriethoxysilane, isooctyltrimethoxysilane, dodecyltrimethoxysilane, octadecyltrimethoxysilane, propyltrimethoxysilane, hexyltrimethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-acryloxypropyltrimethoxysilane, 3-(methacryloxy)propyltriethoxysilane, 3-(methacryloxy)propylmethyldimethoxysilane, 3-(acryloxypropyl)methyldimethoxysilane, 3-(methacryloxy)propyl Pyldimethylethoxysilane, styrylethyltrimethoxysilane, phenyltriethoxysilane, p-tolyltriethoxysilane, vinylmethyldiacetoxysilane, vinyldimethylethoxysilane, vinylmethyldiethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, vinyltriacetoxysilane, vinyltriisopropoxysilane, vinyltriphenoxysilane, vinyltri-t-butoxysilane, vinyltris(isobutoxy)silane, vinyltriisopropenoxysilane, vinyltris(2-methoxyethoxy)silane, diisopropylethylamine phenyltrimethoxysilane (N,N-Diisopropylethylamine 4. The polyimide varnish according to claim 3, comprising at least one selected from the group consisting of N-phenyl-3-aminopropyltrimethoxysilane (PAPTES), N-phenyl-3-aminopropyltrimethoxysilane (N-phenyl-3-aminopropyltrimethoxysilane ...

5. The dianhydride monomer is selected from the group consisting of pyromellitic dianhydride (PMDA), biphenyltetracarboxylic dianhydride (BPDA), benzophenonetetracarboxylic dianhydride (BTDA), oxydiphthalic dianhydride (ODPA), diphenylsulfone-3,4,3',4'-tetracarboxylic dianhydride (DSDA), bis(3,4-dicarboxyphenyl)sulfide dianhydride, 2,2-bis(3,4-dicarboxyphenyl)-1,1,1,3,3,3-hexafluoropropane dianhydride, 2,3,3',4'-benzophenonetetracarboxylic dianhydride, bis(3,4-dicarboxyphenyl)methane dianhydride, 2,2-bis(3,4-dicarboxyphenyl)propane dianhydride, p-phenylenebis(trimeritic monoester acid anhydride), p-biphenylenebis (trimeritic monoester acid anhydride), m-terphenyl-3,4,3',4'-tetracarboxylic dianhydride, p-terphenyl-3,4,3',4'-tetracarboxylic dianhydride, 1,3-bis(3,4-dicarboxyphenoxy)benzene dianhydride, 1,4-bis(3,4-dicarboxyphenoxy)benzene dianhydride, 1,4-bis(3,4-dicarboxyphenoxy)biphenyl 2. The polyimide varnish according to claim 1, comprising at least one selected from the group consisting of 2,3,6,7-naphthalenetetracarboxylic dianhydride, 1,4,5,8-naphthalenetetracarboxylic dianhydride, and 4,4'-(2,2-hexafluoroisopropylidene)diphthalic dianhydride.

6. The diamine monomer is 1,4-diaminobenzene (PPD), 4,4'-diaminodiphenyl ether (ODA), 2,2-bisaminophenoxyphenylpropane (BAPP), metaphenylenediamine, 3,3'-dimethylbenzidine, 2,2'-dimethylbenzidine, 2,4-diaminotoluene, 2,6-diaminotoluene, 3,5-diaminobenzoic acid (DABA), 3,4'-diaminodiphenyl ether, 4,4'-diaminodiphenylmethane (MDA), 3,3'-dimethyl-4,4'-diaminobiphenyl, 2,2'-dimethyl-4 ,4'-diaminobiphenyl (m-tolidine), 2,2'-bis(trifluoromethyl)-4,4'-diaminobiphenyl, 3,3'-dimethyl-4,4'-diaminodiphenylmethane, 3,3'-dicarboxy-4,4'-diaminodiphenylmethane, 3,3',5,5'-tetramethyl-4,4'-diaminodiphenylmethane, bis(4-aminophenyl)sulfide, 4,4'-diaminobenzanilide, 3,3'-dimethoxybenzidine, 2,2'-dimethoxybenzidine, 3,3'-diaminodiphenyl ether, 3,3'-dia aminodiphenyl sulfide, 3,4'-diaminodiphenyl sulfide, 4,4'-diaminodiphenyl sulfide, 3,3'-diaminodiphenyl sulfone, 3,4'-diaminodiphenyl sulfone, 4,4'-diaminodiphenyl sulfone, 3,3'-diaminobenzophenone, 4,4'-diaminobenzophenone, 3,3'-diamino-4,4'-dichlorobenzophenone, 3,3'-diamino-4,4'-dimethoxybenzophenone, 3,3'-diaminodiphenylmethane, 3,4'-diaminodiphenylmethane, 2,2-bis(3-amino phenyl)propane, 2,2-bis(4-aminophenyl)propane, 2,2-bis(3-aminophenyl)-1,1,1,3,3,3-hexafluoropropane, 2,2-bis(4-aminophenyl)-1,1,1,3,3,3-hexafluoropropane, 3,3'-diaminodiphenyl sulfoxide, 3,4'-diaminodiphenyl sulfoxide, 4,4'-diaminodiphenyl sulfoxide, 1,3-bis(3-aminophenyl)benzene, 1,3-bis(4-aminophenyl)benzene, 1,4-bis(3-aminophenyl)benzene, 1,4-bis(4-aminophenyl)benzene, 1,3-bis(4-aminophenoxy)benzene (TPE-R), 1,4-bis(3-aminophenoxy)benzene (TPE-Q), 1,3-bis(3-aminophenoxy)-4-trifluoromethylbenzene, 3,3'-diamino-4-(4-phenylphenoxy)benzophenone, 3,3'-diamino-4,4'-di(4-phenylphenoxy)benzophenone, 1,3-bis(3-aminophenylsulfide)benzene, 1,3-bis(4-aminophenylsulfide)benzene, 1,4-bis(4-aminophenylsulfide) 1,3-bis(3-aminophenylsulfone)benzene, 1,3-bis(4-aminophenylsulfone)benzene, 1,4-bis(4-aminophenylsulfone)benzene, 1,3-bis[2-(4-aminophenyl)isopropyl]benzene, 1,4-bis[2-(3-aminophenyl)isopropyl]benzene, 1,4-bis[2-(4-aminophenyl)isopropyl]benzene, 3,3'-bis(3-aminophenoxy)biphenyl, 3,3'-bis(4-aminophenoxy)biphenyl, 4,4'-bis(3-aminophenoxy)biphenyl, 4,4'-bis(4-aminophenoxy)biphenyl, bis[3-(3-aminophenoxy)phenyl]ether, bis[3-(4-aminophenoxy)phenyl]ether, bis[4-(3-aminophenoxy)phenyl]ether, bis[4-(4-aminophenoxy)phenyl]ether, bis[3-(3-aminophenoxy)phenyl]ketone, bis[3-(4-aminophenoxy)phenyl]ketone, bis[4-(3-aminophenoxy)phenyl]ketone, bis[4-(4-aminophen bis[3-(3-aminophenoxy)phenyl]sulfide, bis[3-(4-aminophenoxy)phenyl]sulfide, bis[4-(3-aminophenoxy)phenyl]sulfide, bis[4-(4-aminophenoxy)phenyl]sulfide, bis[3-(3-aminophenoxy)phenyl]sulfone, bis[3-(4-aminophenoxy)phenyl]sulfone, bis[4-(3-aminophenoxy)phenyl]sulfone, bis[4-(4-aminophenoxy)phenyl]sulfone 2,2-bis[3-(3-aminophenoxy)phenyl]propane, 2,2-bis[3-(4-aminophenoxy)phenyl]propane, 2,2-bis[4-(3-aminophenoxy)phenyl]propane, 2,2-bis[3-(3-aminophenoxy)phenyl]sulfone, bis[3-(3-aminophenoxy)phenyl]methane, bis[3-(4-aminophenoxy)phenyl]methane, bis[4-(4-aminophenoxy)phenyl]methane, 2,2-bis[3-(3-aminophenoxy)phenyl]propane, The polyimide varnish according to claim 1, comprising at least one member selected from the group consisting of 2,2-bis[3-(4-aminophenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane, 2,2-bis[4-(3-aminophenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane, 2,2-bis[4-(4-aminophenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane, and 2,2-bis[4-(4-aminophenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane.

7. 2. The polyimide varnish according to claim 1, wherein the polyamic acid contains polymerized units of pyromellitic dianhydride (PMDA) and 4,4'-diaminodiphenyl ether (ODA).

8. The polyimide varnish further comprises an organic solvent, 2. The polyimide varnish according to claim 1, wherein the organic solvent comprises at least one selected from the group consisting of N-methyl-pyrrolidone (NMP), N,N'-dimethylformamide (DMF), N,N'-diethylformamide (DEF), N,N'-dimethylacetamide (DMAc), dimethylpropanamide (DMPA), N,N-diethylacetamide (DEAc), dimethylsulfoxide (DMSO), 3-methoxy-N,N-dimethylpropanamide (KJCMPA), p-chlorophenol, o-chlorophenol, γ-butyrolactone (GBL), diglyme, and naphthalene.

9. 2. The polyimide varnish according to claim 1, wherein the polyimide varnish has a polyimide solids content of 10 to 50% by weight.

10. The polyimide varnish according to claim 9, wherein the nanosilica is contained in an amount of 4 to 30 parts by weight based on 100 parts by weight of the polyimide solid content contained in the entire polyimide varnish.

11. The polyimide varnish according to claim 1 , wherein the polyimide varnish has a haze of 1.5% or less.

12. The polyimide varnish was heated at 30° C. for 1 s. -1 2. The polyimide varnish according to claim 1, wherein the viscosity of the polyimide varnish is from 500 cP to 20,000 cP when measured under a shear rate condition of 1000 rpm.

13. A polyimide cured product obtained by curing the polyimide varnish according to any one of claims 1 to 12.

14. The polyimide cured material according to claim 13, wherein the voltage endurance characteristic of the polyimide cured material, which is the time that the insulating material can withstand a predetermined voltage according to IEC-60851-5, is 300 minutes or more.

15. A polyimide coating comprising the polyimide cured product according to claim 13.

16. An electric wire comprising the polyimide coating of claim 15.

Citation Information

Patent Citations

  • Partial discharge resistant coating and insulation wire

    JP2017095547A

  • Method for producing modified silica fine particle dispersion

    JP2020147465A

  • Composition, method for producing same, cured body and metal base substrate

    WO2022075226A1

  • Polyamic acid composition and method for preparing same

    WO2023075411A1